Soil phosphorus of stable fraction differentially associate with carbon in the tropical forest and savanna of eastern Cameroon. Issue 6 (2nd November 2017) - Sugihara, Soh; Shibata, Makoto; Mvondo-Ze, Antoine D.; Araki, Shigeru; Kosaki, Takashi; Funakawa, Shinya
ABSTRACT: The forest–savanna transition zone, which contains nutrient-poor soils (Oxisols), is found throughout central Africa. To evaluate the effect of deforestation on soil phosphorus dynamics, which regulate the plant growth in this area, we quantified the relationship between phosphorus (P) and carbon (C) in different fractions and compared their relationship to forest and savanna (deforested vegetation) in eastern Cameroon. We analyzed the P, C, and nitrogen (N) contents of soil using the physical fractionation method (0.25–2.0 mm as macro-particulate organic matter [M-POM]; 0.053–0.25 mm as micro-POM; and <0.053 mm as Clay+silt) in different land management (young and old forests and annual and perennial grass savannas at 100-cm soil depth). We found larger soil P stock in forests (4.7–4.9 Mg P ha −1 ) than that in savannas (3.4–4.0 Mg P ha −1 ), though soil C and N stocks were similar between the vegetation. We also observed lower soil P stock in the active fraction (M-POM) with its higher C:P and lower C:N ratio in forest surface layer (0–10 cm), indicating that forests have lower available soil P. By using the regression analysis, we found a clear relationship between P and C in the stable fraction (Clay+silt) of the upper layer (0–40 cm) for each land management, and the coefficient of the regression was clearly different between the forest and savanna. It indicates that a more chemically complex organic P form of the stable fraction exists in forest soil than in savanna soil. These results indicate that the deforestation (savannazation) affect the active and stable P dynamics and it should cause the lower soil P stock of the upper layer in savanna than in forest.